Effect of Training on Performance at Darmaga Sunda Resto - Idham Sakti Wibawa; Ilham Fajri (Universitas Pendidikan Indonesia, 2023)
This study aims to see how much influence training has on the performance of employees at Darmaga Sunda Resto. The restaurant has identified a need for improved service quality and operational efficiency, which can be achieved through effective training.The research method used is a quantitative method involving employees from various departments at Darmaga Sunda Resto. Data was collected through a specially designed questionnaire to measure employees' perceptions of the training they received and its impact on their performance. The sample of this research is all employees, totaling 17 respondents.The results of this study indicate that training has a significant positive effect on employee performance at Darmaga Sunda Resto. It was found that employees who received proper and structured training tended to show improvement in their ability to provide quality service to customers. Training also contributes to increasing employee productivity, knowledge and work skills.These findings indicate that investing in appropriate training can improve overall individual and organizational performance in the hotel and restaurant industry sector. The recommendation for Darmaga Sunda Resto is to continue to focus on a quality training program, which includes developing employees' technical and interpersonal skills, as well as increasing efficiency and customer satisfaction.